Analysis of Mathematical Critical Thinking Skills in Non-Formal Learning Based on Learning Assistance - Setiana, Dafid Slamet; Hakim, Septian Rahman; Booribon, Gumpanat (Studies in Learning and Teaching, 2025)
This research aims to analyze students' critical thinking skills in non-formal learning based on learning assistance for elementary school level students in the gemstone craft center area of Sukodono Village. The type of research is descriptive research with a quantitative approach. The research subjects were elementary school age students who had previously been provided with non-formal learning assistance using techniques to stimulate critical thinking. Test results are analyzed based on scoring guidelines and critical thinking indicators, then converted into scores and categorized based on critical thinking skills criteria. The novelty of this research is that the analysis of critical thinking skills in non-formal learning has never been carried out before. Analysis of critical thinking skills indicators shows the value of the Focus indicator of 85.7 (very high); Reason indicator of 63.2 (high); Inference indicator of 78.5 (high); Situation indicator of 73.8 (high); Clarity indicator of 70.4 (high); Overview indicator of 58.7 (fair). This indicates that non-formal learning based on learning assistance is useful in improving aspects of knowledge, especially in critical thinking skills. Therefore, non-formal education can be used as an alternative method in increasing the potential of students as a support for formal learning.